PENDEKATAN DEEP LEARNING BERBASIS KECERDASAN ARTIFICIAL PADA PEMBELAJARAN BAHASA INGGRIS KELAS 3 SD - Cicin Maenawati; Muhamad Sofian Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of an artificial intelligence-based Deep Learning approach on English learning outcomes of third-grade elementary school students. The research employed a quantitative approach using a quasi- experimental design. The research subjects consisted of 45 students from two elementary schools, namely SDS Alam Madinah School and SD Swasta Plus Ar Rahmaniyah. English learning activities were conducted using Duolingo as an artificial intelligence- based learning application. Data were collected through pretest and posttest instruments, while data analysis was performed using SPSS, including normality tests, homogeneity tests, t-tests, F-tests, multiple linear regression analysis, and correlation analysis. The results indicate a significant improvement in students’ English learning outcomes after the implementation of the AI-based Deep Learning approach. Statistical analysis confirms that the approach has a positive and significant effect on learning outcomes both partially and simultaneously. Therefore, the AI-based Deep Learning approach is proven to be effective in elementary English learning and can be recommended as an innovative instructional strategy in primary education.